PERANG UHUD (Suatu Analisis Historis Sebab-Sebab Kekalahan Umat Islam) - Iqbal, Iqbal (RIHLAH, 2014)
This paper explain about Uhud War, an accident was happening on Syawwal 07th, 03 H./625 M. On the war,Â  two groups were fighting each other,Â  Moslems and Quraisy Clan.Â  This paper explain on theÂ  history side and doing on qualitative research typeÂ  byÂ  library research. UhudÂ  War isÂ  the second war afterÂ  Badar War. On thisÂ  war, Moslem was losing. This drubbingÂ  was happening cause some Moslems wasnât loyal to prophetâs command. ThisÂ  accidentÂ  made Hamzah died and prophet MuhammadÂ  saw. was hurt by Quraisy Clan. So, Uhud War is the war had been a training for Moslems, including some Moslems supporter had gotten out from Moslemâs line. This group was commanded by Abdullah Bin Ubay. TheyÂ  were going back to Madinah before the war happened. This accident absolutely made account of Moslems had decreased. At the beginning of war, prophet MuhammadÂ  hadÂ  thousand warriors, but after this accident, prophet Muhammad had seven hundred warriors. This accident absolutely had decreased to the power of warriors.